Financial Management Analysis Of Mantikulore Sub District Palu City Government - Feriyanto Latjindung; Rudin; Muhammad Darma Halwi; Moh. Agus Lamakarate; Fadila Almahdali; Zakir Muhammad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Mantikulore Sub District, Palu City Government, which is an important element in the Regional Government Structure and is the leading administrative Regional Apparatus Organization in implementing public policies and services. Public sector financial management includes budget planning, budgeting and allocation, control and evaluation, and reporting and auditing that focuses on accountability. The research method used is descriptive qualitative with a case study approach, which involves in-depth interviews and direct observation in Mantikulore Sub District. The results of the study indicate that the public sector financial management of Mantikulore Sub District has been implemented according to the stages of budget planning, budgeting and allocation, control and evaluation, and reporting and auditing that apply and has reflected the principles of public accountability, although it still needs to improve Human Resources and Support Systems. The recommendations from this study are the need to increase the capacity of human resources for planning and financial management through continuous training, and further increase community participation in the development planning deliberations, as well as the need to optimize the use of information systems to increase transparency and accountability.